Reply to Lounise Morissette:
Great job breaking down the problem step-by-step, Lounise! Your explanation makes it easy to follow how to combine like terms and isolate the variable. Here’s a similar example for practice:
Example:
Step 1:
We start with the equation: \(12y - 5y + 3y = 27\).
First, combine the like terms (all involving \(y\)) by subtracting and adding the coefficients:
\((12 - 5 + 3)y = 27\)
Calculating the coefficients:
\((12 - 5 + 3)y = 10y = 27\).
Step 2:
Now, to isolate \(y\), divide both sides of the equation by 10:
\(\frac{10y}{10} = \frac{27}{10}\).
Simplifying gives:
\(y = 2.7\).
So, the solution to this example is \(y = 2.7\). If you have any questions or need further clarification, feel free to ask!